GLP-1 Analogs and DPP-4 Inhibitors in Type 2 Diabetes Therapy: Review of Head-to-Head Clinical Trials - Gilbert, Matthew P.; Pratley, Richard E. (Frontiers in Endocrinology, 2020)
The incretin hormones glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) are released from specialized enteroendocrine cells in response to the appearance of nutrients in the gut. They have a number of effects that facilitate glucose regulation, including enhancing insulin secretion while suppressing glucagon secretion (GLP-1) in a glucose dependent manner. In patients with type 2 diabetes (T2DM), an impaired insulin response to GLP-1 and GIP contributes to hyperglycemia. Dipeptidyl peptidase-4 (DPP-4) inhibitors block the metabolism of GLP-1 and GIP to enhance levels of the active hormones. In clinical trials, DPP-4 inhibitors have demonstrated a modest effect on glycemic control. They are generally well-tolerated, weight neutral and do not increase the risk of hypoglycemia. GLP-1 receptor agonists (GLP-1 RA) are peptide derivatives of either exendin-4 or human GLP-1 designed to resist the catalytic activity of DPP-4 and have a prolonged half-life. In clinical trials, they have demonstrated superior efficacy to many oral antihyperglycemic drugs, weight loss and a low risk of hypoglycemia. However, GI adverse events, particularly nausea, vomiting, and diarrhea are seen. Both DPP-4 inhibitors and GLP-1 RAs have demonstrated safety in robust cardiovascular outcome trials, while several GLP-1 RAs have been shown to significantly reduce the risk of major adverse cardiovascular events in persons with T2DM with pre-existing CVD. Several clinical trials have directly compared the efficacy and safety of DPP-4 inhibitors and GLP-1 RAs. These studies have generally demonstrated that the GLP-1 RA provided superior glycemic control and weight loss relative to the DPP-4 inhibitor. Both treatments were associated with a low and comparable incidence of hypoglycemia, but treatment with GLP-1 RAs were invariably associated with a higher incidence of GI adverse events. According to current clinical guidelines, GLP-1RA and DPP-4 inhibitors are both indicated for the glycemic management of patients with T2DM across the spectrum of disease. GLP-1RA may be preferred over DPP- 4 inhibitors for many patients because of the greater reductions in hemoglobin A1c and weight loss observed in the clinical trials. Among patients with preexisting CVD, GLP-1 receptor agonists with a proven CV benefit are indicated as add-on to metformin therapy.